2020
DOI: 10.1111/1468-2230.12506
|View full text |Cite
|
Sign up to set email alerts
|

Border Problems: Mapping the Third Border

Abstract: The Internet has become the site of economically relevant objects, events and actions, as well as the source of potential risks to the financial systems. This article builds on a metaphor of 'border problems' in financial regulation, exploring a 'third border' between the 'real world' and 'cyberspace'-a virtual domain of human interaction facilitated and conditioned by digital communications systems. Reviewing the 'cyber-sovereignty' debate and surveying the divergent approaches now emerging along geo-politica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Malby studied [8] the business model based on blockchain and its regulation and concluded that blockchain can bring continuous innovation to business models under regulation; Olatunji [9] explored revolutionary changes brought by blockchain to traditional industries; Reddy [10] studied logistics and distance effects of e-commerce in EU market, and logistics affects development ; Ezuwore-Obodoekwe [11] studied problem of logistics path optimization in context of epidemic; Yao et al [12]studiedthe prospect of blockchain application in supply chain and its commercial value are studied. Allen et al [13] discussed in detail problems encountered in payment and proposed solution of settlement by DECP, LIBRA, etc. ; Balamurugan et al [14] discussed application of blockchain in supply chain in field of customs compliance and analyzed advantages of using blockchain with projects that have been carried out at home and abroad and gave suggestions on information collaboration and cooperation between government and enterprises; Brynjolfsson et al [15] took e-commerce between China and Europe as a object of research and proposed application of blockchain in supply chain.…”
Section: Related Workmentioning
confidence: 99%
“…Malby studied [8] the business model based on blockchain and its regulation and concluded that blockchain can bring continuous innovation to business models under regulation; Olatunji [9] explored revolutionary changes brought by blockchain to traditional industries; Reddy [10] studied logistics and distance effects of e-commerce in EU market, and logistics affects development ; Ezuwore-Obodoekwe [11] studied problem of logistics path optimization in context of epidemic; Yao et al [12]studiedthe prospect of blockchain application in supply chain and its commercial value are studied. Allen et al [13] discussed in detail problems encountered in payment and proposed solution of settlement by DECP, LIBRA, etc. ; Balamurugan et al [14] discussed application of blockchain in supply chain in field of customs compliance and analyzed advantages of using blockchain with projects that have been carried out at home and abroad and gave suggestions on information collaboration and cooperation between government and enterprises; Brynjolfsson et al [15] took e-commerce between China and Europe as a object of research and proposed application of blockchain in supply chain.…”
Section: Related Workmentioning
confidence: 99%
“… 2 Aksoy, Eichengreen and Saka [ 1 ] show that past epidemics induced changes in banking practice away from interpersonal interaction at bank branches and toward online, Internet and cell-phone-based banking. Crosman [ 2 ] observed early in the pandemic that 35 percent of customers surveyed had increased their usage of online banking during COVID-19. The unanswered question, as Crosman notes, is whether the shift will last.…”
mentioning
confidence: 99%
“…Open-banking protocols are one way of addressing this problem (again, see below). Carstens [ 2 ] reports data for a selection of BigTechs in 2018, indicating that finance accounts for about 10 percent of their total revenues, which suggests that the potential scope for cross-subsidization is considerable.…”
mentioning
confidence: 99%